2015
DOI: 10.11648/j.sjph.20150303.24
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practices of Hand Washing and Glove Utiliz ation Among the Health Care Providers of Shenen Gibe Hospital, South West Ethiopia

Abstract: Background Nosocomial or Hospital Acquired infections-Is an infection that is neither present nor incubating at the time the patient came to the health care facility(hospital). Nosocomial refers to the association between care and the subsequent onset of infection. To prevents this infection open hand washing and glove utilization practice is simple and an important method. Objectives: To investigate the knowledge and practice of hand washing and glove utilization among the health care workers of Shenen Gibe H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
1
2
1
Order By: Relevance
“…This finding was lower than that in the study conducted at Bahir Dar City Administration Health Institutions, which was about 50.8%. But the overall of hand washing practice of this study finding was relatively similar to a study conducted in Bahir Dar City Administration [12], Shenen Gibe Hospital [13], and Southwest Nigeria Tertiary Hospital [14], which was 69%, 68.8%, and 69.9%, respectively. However, it was higher than a study conducted in Sri Lanka which showed that only 10% had overall good practices, while 27% had moderate practices and majority (62.5%) were seen to have poor hand hygiene practices [15].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This finding was lower than that in the study conducted at Bahir Dar City Administration Health Institutions, which was about 50.8%. But the overall of hand washing practice of this study finding was relatively similar to a study conducted in Bahir Dar City Administration [12], Shenen Gibe Hospital [13], and Southwest Nigeria Tertiary Hospital [14], which was 69%, 68.8%, and 69.9%, respectively. However, it was higher than a study conducted in Sri Lanka which showed that only 10% had overall good practices, while 27% had moderate practices and majority (62.5%) were seen to have poor hand hygiene practices [15].…”
Section: Discussionsupporting
confidence: 84%
“…In this study, out of 91 health professionals, 60 (65.93%) were knowledgeable and 31 (34.07%) were not knowledgeable. This result was lower than the result of a study done at Shenen Gibe Hospital, Southeast Ethiopia, in which 82.9% had good knowledge and 17.1% had poor knowledge [13], and comparable with the study done at Jimma University Hospital on hand washing among nursing staffs in which 71.6% had good knowledge while the rest 28.4% had poor knowledge [11]. This might be due to the time gap, homogeneity of the study participants, and status of the hospital.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Most of the participants in the present study (83.2%) said that they wash their hands before and after contact with patients. This finding was higher than those of previous studies conducted in Ethiopia [ 1 , 15 , 31 , 32 ], Nigeria [ 14 , 33 ], Sri Lanka [ 34 ], and Saudi Arabia [ 19 ]. Other international studies reported moderate hand washing practice [ 27 , 35 ] and addressed the importance of hand washing among different populations [ 22 , 27 ].…”
Section: Discussioncontrasting
confidence: 69%